Deconstruction Of Deliberation Implementation And The Populist Meaning In The Perspective Of Prophetic Democracy In The Implementation Of Pancasila - Megawati Megawati (Journal of Transcendental Law, 2019)
Purpose of the study: This article aims at evaluating the implementation of popular sovereignty as a forum for deliberation in the election of regional heads as the implementation of the fourth precept of Pancasila.Methodology: This study was conducted by using the method of descriptive philosophical normative study. As a secondary legal material, this paper garnered information from literature, papers, journals, and other related studies.Main Findings: In the implementation of general election of regional heads, democracy in Article 18 paragraph (4) of the 1945 Constitution is not limited to direct or indirect election by the people. The election of regional heads can be carried out in conformity to the identity of Indonesia people.Applications of this study: This study can be beneficial to the government in reexamining the policy of the direct regional head general election considering that in the interpretation of Article 18 paragraph (4) of the 1945 Constitution, general election does not have to be implemented directly.The policy of the direct regional head general electionNovelty/Originality of this study: The notion as regards the implementation of the indirect regional head general election will have a less negative impact compared to the direct election.